Women and Their Mothers-in-Law: Triangles, Ambiguity, and Relationship Quality. (29th November 2019) - Greif, Geoffrey L; Woolley, Michael E
Abstract: Each marriage is the beginning of multiple intergenerational in-law relationships. Drawing on a survey of 351 women about their relationships with their mothers-in-law (MILs), this article reports on the impact of family triangles and boundary ambiguity on the quality of the relationship. In a three-block regression analysis, predicting a seven-item relationship quality scale, the first block included six demographic variables. The second and third blocks included three survey items each of reported relationship triangles and boundary ambiguity in a woman's interactions with her MIL. Results revealed that although the couple having children predicted worse relationship quality in the demographic block, that result was no longer significant once family triangle measures were entered. All three measures of boundary ambiguity were also significant. The three measures of boundary ambiguity eclipsed two of the three family triangles when entered in the third block, leaving only the daughter-in-law feeling comfortable going directly to the MIL about important issues still significant.